2002
DOI: 10.1211/0022357021778844
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological properties and SAR of new 1,4-disubstituted piperazine derivatives with hypnotic-sedative activity

Abstract: Preparation, pharmacological properties and structure-activity relationships of new pyrimidyl-piperazine derivatives, exhibiting sedative and hypnotic activity in mice, are reported. The hypnotic activity of the compounds was comparable with that of zopiclone (the known hypnotic-sedative agent), their interaction with ethanol, however, being much lower. The obtained results suggested that zopiclone and pyrimidylpiperazines 2, 4 and 5 exerted their pharmacological activity through a different mechanism - zopicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Inserting selected piperazine moieties into the oxypropanolamine side chain increases the antagonistic α 1 -adrenergic properties [5,6]. Arylpiperazine derivatives of this group also confer intraocular pressure lowering effects [7] and display considerable affinity for the serotonergic 5-HT receptors [8,9]. It was suggested that the isopropanolamine unit present in peptidic drugs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Inserting selected piperazine moieties into the oxypropanolamine side chain increases the antagonistic α 1 -adrenergic properties [5,6]. Arylpiperazine derivatives of this group also confer intraocular pressure lowering effects [7] and display considerable affinity for the serotonergic 5-HT receptors [8,9]. It was suggested that the isopropanolamine unit present in peptidic drugs (e.g.…”
Section: Introductionmentioning
confidence: 99%